Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36

3 answers

Step 1: Distribute the 3 to the terms inside the parentheses.
3x - 12 + 5x = 9x - 36

Step 2: Combine like terms on the left side of the equation.
8x - 12 = 9x - 36

Step 3: Subtract 8x from both sides to isolate the x term on the right side.
-12 = x - 36

Step 4: Add 36 to both sides to isolate the x term on the left side.
24 = x

So the solution to the equation is x = 24.
A Subtraction Property of EqualitySubtraction Property of Equality
B Commutative Property of AdditionCommutative Property of Addition
C Addition Property of EqualityAddition Property of Equality
D Additive Inverse Property
C. Addition Property of Equality
Similar Questions
  1. 21 of 2321 of 23 Items19:35 Question Consider the sequence of steps to solve the equation: 3(x − 4) + 5x = 9x − 36 Given ⇒
    1. answers icon 1 answer
  2. Consider the sequence of steps to solve the equation:5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3
    1. answers icon 5 answers
    1. answers icon 1 answer
    1. answers icon 1 answer
more similar questions